BARBIE. Bayesian Analysis for Remote Biosignature Identification on exoEarths. III. Introducing the KEN - Natasha Latouf; Michael D. Himes; Avi M. Mandell; Michael Dane Moore; Vincent Kofman; Geronimo L. Villanueva; Chris Stark (The Astronomical Journal)
We deploy a newly generated set of geometric albedo spectral grids to examine the detectability of methane (CH _4 ) in the reflected-light spectrum of an Earth-like exoplanet at visible and near-infrared (NIR) wavelengths with a future exoplanet imaging mission. By quantifying the detectability as a function of signal-to-noise ratio (SNR) and molecular abundance, we can constrain the best methods of detection with the high-contrast space-based coronagraphy slated for the next-generation telescopes such as the Habitable Worlds Observatory. We used 25 bandpasses between 0.8 and 1.5 μ m. The abundances range from a modern-Earth level to an Archean-Earth level, driven by abundances found in available literature. We constrain the optimal 20%, 30%, and 40% bandpasses based on the effective SNR of the data, and investigate the impact of spectral confusion between CH _4 and H _2 O on the detectability of each one. We find that a modern-Earth level of CH _4 is not detectable, while an Archean-Earth level of CH _4 would be detectable at all SNRs and bandpass widths. Crucially, we find that CH _4 detectability is inversely correlated with H _2 O abundance, with the required SNR increasing as H _2 O abundance increases, while H _2 O detectability depends on CH _4 abundance and the selected observational wavelength, implying that any science requirements for the characterization of Earth-like planet atmospheres in the visible–NIR should consider the abundances of both species in tandem.